2000
DOI: 10.1002/1097-0320(20001001)41:2<123::aid-cyto7>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor‐induced calcium responses in astroglia

Abstract: Background:The objective of this study was to characterize and quantitate the calcium responses to cholinergic stimulation in individual primary rat cortical astrocytes and human 132 1N1 astrocytoma cells. Materials and Methods:The fluorescent calcium probe Indo-1 AM and an attached cell analysis and sorting (ACAS) instrument were used to quantitate calcium responses in these cells. Results: A concentration-dependent response to carbachol was seen in both cell types. However, carbachol was more potent and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 28 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…Over the past few years we have identified several intracellular pathways by which activation of muscarinic M3 receptors induces proliferation of astroglial cells (Guizzetti et al , 1998Catlin et al 2000b;Guizzetti and Costa 2000a, 2002Yagle et al 2001). We also found that ethanol inhibits carbachol-induced DNA synthesis in astroglial cells and that only selective signaling molecules activated by carbachol are affected by concentrations of ethanol capable of inhibiting cell proliferation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Over the past few years we have identified several intracellular pathways by which activation of muscarinic M3 receptors induces proliferation of astroglial cells (Guizzetti et al , 1998Catlin et al 2000b;Guizzetti and Costa 2000a, 2002Yagle et al 2001). We also found that ethanol inhibits carbachol-induced DNA synthesis in astroglial cells and that only selective signaling molecules activated by carbachol are affected by concentrations of ethanol capable of inhibiting cell proliferation.…”
Section: Discussionmentioning
confidence: 77%
“…Such mitogenic effect appears to be mediated by two intracellular signaling pathways, one leading to the activation of phospholipase C (PLC), protein kinase C (PKC) e and mitogen-activated protein kinase (MAPK), and another involving phosphatidylinositol-3-kinase (PI-3K), PKC f, 70-kDa ribosomal S6 kinase (p70S6K) and nuclear factor-jB (NF-jB) (Guizzetti et al 1998(Guizzetti et al , 2003aCatlin et al 2000b;Costa 2000a, 2001;Yagle et al 2001). Selective inhibition of each of these enzymes leads to inhibition of carbachol-induced cell proliferation, suggesting that both pathways are required for carbacholinduced DNA synthesis.…”
mentioning
confidence: 99%
“…In the experiment of Fig. 3A, the 1 mM CCh-induced Ca 2+ transient was blocked by the application of 10 lM (Catlin et al, 2000) atropine, while in Fig. 3C 10 lM (Hösli et al, 2001) muscarine evoked a plateau-type response that could be fully blocked by 10 lM atropine, too.…”
Section: Mechanism Of the Cholinergic Effect On The Astrocytesmentioning
confidence: 83%
“…Although the heterogeneity of the CCh-evoked responses was pronounced in these experiments, 50-100 lM CCh regularly evoked Ca 2+ transients in the responding cells. Generally, these values are higher than most of those used in other brain preparations, although in some cases applications of even millimolar CCh concentrations for evoking maximal cholinergic response have also been reported (Shao and McCarthy, 1995;Catlin et al, 2000). In the present experiments the certainly supramaximal 1 mM CCh was chosen in order to ensure well-detectable cytoplasmic Ca 2+ concentration increases in all astrocytes that were sensitive to cholinergic stimulation.…”
Section: Characterisation Of the Carbachol-induced Ca 2+ Concentratiomentioning
confidence: 91%
See 1 more Smart Citation